Law Enforcement on Criminal Acts of Spreading Fake News through the Internet Media Reviewed from Law Number 19 Year 2016 Concerning Information and Electronic Transactions (Study at North Sumatra Police) - Agung Perdana Ginting; M. Arif Sahlepi Lubis; Dina Andiza (Polit Journal Scientific Journal of Politics, 2022)
Hoaxes are categorized as unlawful acts, currently illegal acts in cyberspace are a very worrying phenomenon, considering the act of breaking into credit cards by shopping online, fraud, terrorism, and has become the activity of criminals in cyberspace. This research is an empirical legal research, where in this study the author examines the role of the North Sumatra Regional Police Agency in carrying out law enforcement against criminals who spread false news. The results of this study conclude that the problem that causes hoaxes is the habit of most people who want to quickly share information, so this trait is also carried over in the way they communicate using social media. In relation to criminal sanctions against spreading false news that can harm consumers or express hatred, they may be subject to a maximum imprisonment of 6 (six) years and/or a maximum fine of Rp. 1,000,000,000 (one billion rupiah). In this study it can be concluded that overall the North Sumatra Police have carried out their authority in providing assistance and protection to victims quite well.